Sinopsis del estudio de la iconografía de la "Nueva corónica y buen gobierno" escrita por Felipe Guamán Poma de Ayala - González Vargas, Carlos; Rosati Aguerre, Hugo; Sánchez Cabello, Francisco (Historia, 2001)
Through the study of the work of Felipe Wuaman Poma and the through observation of the prints in it included, we intend to achieve an exhaustive comprehension of the thinking patterns, principles and values of the indigenous peoples of the Andean world. We called the methodology applied "laterality study". The latter consists of the observation and analysis of the ilustrations, represented in the prints according to a symbolic arrangement, based on indigenous models of thinking with a hierarchical character -thus linking the sacred world with the profane- that determine the position of divinities, characters and objects according to constants of significance such as importance (social role?), position (social or economic?), sex (gender) and quality (qualification?). Such "laterality principle" is still valid in current Weltanschaungs found in the Andean and South Andean Regions.